2010
DOI: 10.1007/s11695-010-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Carbohydrate-Restricted Diet for Weight Loss in Severely Obese Women

Abstract: Short-term RD was more efficient than CD regarding quick weight loss and waist circumference reduction, which may favor gastroplasty. Also, RD did not lead adverse metabolic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…It is a retrospective cohort study with all the disadvantages of these studies. The untreated group defined by early‐onset of lack of tolerance of rimonabant provides a small self‐selected parallel comparison group but shows weight reductions similar to those seen in a randomised study of dietary therapy in a prebariatric population of 1.7 kg (5).…”
Section: Effects Of Long‐term Treatment With Rimonabant In Morbidly mentioning
confidence: 88%
See 1 more Smart Citation
“…It is a retrospective cohort study with all the disadvantages of these studies. The untreated group defined by early‐onset of lack of tolerance of rimonabant provides a small self‐selected parallel comparison group but shows weight reductions similar to those seen in a randomised study of dietary therapy in a prebariatric population of 1.7 kg (5).…”
Section: Effects Of Long‐term Treatment With Rimonabant In Morbidly mentioning
confidence: 88%
“…Presurgical management of patients due to undergo bariatric surgery typically involves the prescription of a low calorie, low carbohydrate diet to reduce hepatomegaly and fatty liver. In prebariatric patients a trial of 19 patients showed an average 4.4 kg loss with this intervention as opposed to 2.6 kg with calorie restriction (5). In this audit rimonabant therapy resulted in a non‐significant 3% weight loss (4.6 ± 11 kg; 1.7 ± 4 kg/m 2 ) allied with predictable reductions in blood pressure, glucose; and HbA 1c , triglycerides and increased HDL‐C.…”
Section: Effects Of Long‐term Treatment With Rimonabant In Morbidly mentioning
confidence: 99%
“…Moreover, our previous studies have reported that obesity is more prevalent among Asian Indian women as compared to men, specifically after child birth and in the postmenopausal phase [ 52 , 53 ]. Further, the trial duration of 8 weeks in the present study could be a possible limitation, but studies of 1 and 4 weeks duration have been published previously [ 12 , 54 ]. Studies of longer duration should be conducted to evaluate the long-term effect on kidney function, reproductive health, bone matrix and life span.…”
Section: Discussionmentioning
confidence: 98%
“…This study was approved by the Research Ethics Committee of HCFMRP-USP (Protocol number 2937/2007) and it is a continuation of a greater study on severe obesity and low-carbohydrate diet 20 .…”
Section: E T H O D Smentioning
confidence: 99%